Assessment of efficacy and safety of dapsone gel 5% in the treatment of acne vulgaris - Al-Ani, Yasir mansour (AL-Kindy College Medical Journal, 2019)
ABSTRACTBackground : Acne vulgaris is a common skin disease, affecting more than 85% of adolescents and often continuing into adulthood. People between 11 and 30 years of age and up to 5% of older adults. For most patients acne remains a nuisance with occasional flares of unsightly comedones, pustules and nodules. For other less fortunate persons, the sever inflammatory response to Propionibacterium acnes (P.acnes) results in permanent Methods: Disfiguring scars. (1, 2) Stigmata of sever acne cane lead to social ostracism, withdrawal from society and severe psychologic depression (1-4). Result Pathogenesis of acne Traditionally, acne has been thought of as a multifactorial disease of the folliculosebaceous unit, involving excess sebum production, abnormal follicular hyperkeratinization, overgrowth of Propionibacterium acnes, and inflammation (Fig 2). Recent laboratory and clinical investigations into the roles of the innate immune system and extracellular matrix remodeling proteins have shed additional light on this pathogenetic process (5-7). Role of androgens: Activity of type 1 5areductase enzyme was shown to predominate in human sebaceous glands and epidermis. This enzyme is responsible for the conversion of testosterone to the more potent androgen, dihydrotestosterone (DHT). DHT in turn is thought to mediate androgen dependent skin diseases such as acne, hirsutism and androgenetic alopecia (13) The enzyme 5a-reductase type 1 has been studied in those with and without acne and it has been hypothesized that those with acne might have more active 5a-reductase type 1 .(2) Conclusion : The prominent role of hormones in the pathophysiology of acne has long been recognized and corroborated by clinical and experimental observations and therapeutic experience (14). Although acne is not considered a primary endocrine disorder, androgens, such as dihydrotestosterone, dehydroepiandrosterone sulfate, and testosterone, and growth hormone and insulin-like growth factors, have all been implicated in the pathogenesis of acne (15). Corresponding address to : Dr. Yasir Mansour Mohamed Al-Ani Islam Mohammad Nabil El Helou